Main priorities of the state policy of the Republic of Kazakhstan in the formation of historical consciousness - Mukanov, М.Р.; Aidarkozhin, М.А. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2024)
The article attempts to determine the main priorities of the state policy of the Republic of Kazakhstan in the formation of historical consciousness. For this purpose, the analysis of the state programs implemented in this direction is carried out. The need for further work on the formation of historical consciousness is due to the fact that it is an important component of public and source of national self-consciousness, which serves to meet socio-cultural and ideological and personal needs, as well as realising the importance of knowing the history of their country and preserving the historical past for future generations. The process of formation of historical consciousness should become an integral part of the state policy of the Republic of Kazakhstan. The most important direction is education, including the study of not only history, but also the state language, as they are interrelated. At the same time, the effectiveness of formation of historical consciousness depends on teaching methods, and also requires taking into account the specifics of educational institutions, regions, social and national groups. The author considers the existing problems and formulates proposals for their solution. In particular, it is proposed to introduce a pilot project on the use of virtual excursions in the teaching of history, which will help to achieve a conscious attitude to the importance of knowing the history of their country and preserving the historical past for future generations, as well as a number of measures to improve the quality and effectiveness of teaching history and the Kazakh language.